A ação supervisora na escola pública da rede estadual de São Paulo: um estudo de caso - Torres, Lélia Hartmann (2009)
The objective of the study is to discuss the supervision action in public schools in the state schools of São Paulo in the decades of 1970, 1980 and 1990, articulating them to the educational reforms that took place in this period that corresponds to the law in force Federal Law 5692/71, the so called technicist period in the education, Law 7044/82 correspondent to the period of the redemocratization of education and Law 9394/96 that is characterized as the period of neoliberal inspiration in educational reforms. The Supervisor of Education in the State of São Paulo, as member of the supervision team of the Directory of Education is an articulator and mediator for the implemented educational politics and the pedagogical proposals developed by each School Unit. The study includes a literature revision on the thematic with sights to the deepening of its understanding. It also includes a characterization of the supervisor action in the state schools of São Paulo through the gathering of the legal procedures and institutional documents that establish the attributions and requirements for the work. The study of the practice of the Supervisor of Education was carried by the means of an analysis of the visit terms to the school, elaborated by the supervisors during the decades of 1970, 1980 and 1990. The visit terms refer to the register that the supervisor carries through each attendance at the School Unit, indicating what was done during that visit. The activities developed by the supervisors had been categorized to allow its analysis, discussion and considerations.